0 votes
72 views
ago in Other by (-1,675 points)
HI(aq)+KOH(aq)→H2O(l)+KI(aq) express this as a complete ionic equation

Please log in or register to answer this question.

1 Answer

0 votes
ago by (-7,939 points)
H^+(aq) + I^-(aq) + K^+(aq) + OH^-(aq) ==> H2O(l) + K^+(aq) + (I^-)(aq)

The net ionic equation is

H^+(aq) + OH^-(aq) ==> H2O(l)

Related questions

0 votes
1 answer
0 votes
1 answer
asked Aug 25 in Other by megha00 (-7,939 points)
0 votes
1 answer
0 votes
1 answer
asked Dec 18, 2019 in Important Questions by manish56 (-1,675 points)

Categories

...